Demand for money in Singapore in the 1990s. - Lian, Ji Wei. (2008)
The main objective of this paper is to attempt to quantify the money demand relationship in Singapore. Using OLS method, several key variables like income and interest rates affecting money demand were investigated. Dynamics were added to the model through the inclusion of expectations.